The cytoskeletal basis of plant growth and form (London, 1991)
This book is about the shape of plant cells and factors that affect it during development. Its contents are organized from molecular, through cellular, to developmental aspects
Keywords: botany - research,plant cells and tissues,plant cytoskeleton